Kariera agens vice praefectorum praetorio Luciliusa Crispusa i chronologia utworzenia stanowiska wikariusza diecezjalnego w Poncie - Smorczewski, Łukasz (Czasopismo Prawno-Historyczne, 2018)
The aim of the following article is to present chronologically the creation of the position of the diocese vicar in Pontus. The act of creation of the diocese was ascribed to emperor Diocletian according to the previously prevalent concept of historiography. However, this position is currently gradually criticized. The main source material which enables the dating of the territorial reform of the Roman state is the Verona List, which is also called Laterculus Veronensis. The document presents the earliest period of shaping of the diocese structure as well as the subscriptions of the bishops who authorized the decisions taken at the First Council of Nicaea. Besides the aforementioned evidence, another extremely significant source is the prosopographical data from the officials serving in the rank of vicarii and comites provinciarum in the late Roman period. In case of the Pontus diocese, we have at our disposal inscriptions which present the career of Lucilius Crispus as agens vice praefectorum praetorio. A detailed analysis of the epigraphical data facilitated the process of the dating of the term of office of this regional functionary. It can be ascertained that he performed his function at the time of the reign of emperor Galerius (terminus a quo at the end of November 308). His place of residence was in Galatian Ancyra. The next official of this rank was noted in relations between Lactantius and Eusebius of Caesarea during the reign of Licinius (circa 313). This anonymous vice-prefect resided in Nicomedia at the time. Additional data is provided by hagiographic sources which describe the fate of Galatian martyrs and it also made note of two vicars, namely Domitianus and Aggripinus. However, the portrayal of the legal situation in the period of tetrarchy which was presented in the said sources raises reasonable doubts concerning their credibility. Nevertheless, both agentes (Lucilius Crispus and the anonymous vice-prefect of Licinius’) operated in the Black Sea region as extraordinary delegates of the praetorio prefect without the formation of a permanent organ of local administration. The implementation of a diocesan organisation most probably took place during the independent reign of Constantine the Great. Only then was it possible to carry out a consistent and permanent separation of jurisdiction of individual officials who had vice sacra iudicans jurisdiction. A passage, hitherto disregarded by historians, which comes from Vita Constantini points to this. Moreover, it explicitly states the name of the Pontus diocese. It allows the dating of terminus ante quem appointment of the Black Sea regional unit on the 19th of July 325.